The Mediating Effect of Taxpayer Perception in the Relationship between Tax Education and Income Tax Filing Compliance among Small Taxpayers in Mbarara City - Mwesigye, Boaz; Kijjambu, Frederick Nsambu (International Journal of Entrepreneurship, 2024)
This study is about establishing the mediating role of taxpayer perception in the relationship between tax education and income tax filing compliance among small taxpayers in Mbarara city. Materials and Methods: The study used crosssectional research design on a study population of 33,979 small taxpayers with a sample size of 380 respondents in Mbarara city. Systematic random sampling was used to select respondents while data was collected using a questionnaire tool whose validity (Content Validity Index) and reliability (Cronbach’s Alpha) were ascertained before data collection and found to be above 0.70. The collected data was analyzed with the aid of SPSS version 26.0 to generate regression coefficients which were exported to an Online Medgraph Calculator to determine mediation effect, significance and path analysis. Findings: The regression analysis results revealed that taxpayer perception had a significant partial mediating effect (βmd=.366, p<0.05) on the relationship between tax education and income tax filing compliance among small taxpayers in Mbarara city. Based on the findings, the study concludes that efforts aimed at improving taxpayer perceptions play a significant role in strengthening the relationship between tax and income tax filing compliance. Implications to Theory, Practice and Policy: The study recommends a need for the government and tax authorities, in this case, Uganda Revenue Authority to put in place strategies and programs aimed at changing individual perceptions, social understanding and personal motivations regarding income tax filing. Some of these strategies include intensifying tax education and outreach services of the mobile tax office ‘Tujenge Bus Services’ to all locations; introducing basic tax education at earlier stages of formal education such that citizens are informed about their future obligations to file income tax returns; translating all information about income tax filing in different local languages and publishing the same in print format for public access at no cost; and recruiting more tax agents within Mbarara city who can assist small taxpayers in income tax filing at a reasonable fee. The assumptions of the Theory of Reasoned Action, Social Influence Theory and Motivational Posturing Theory could also be relevant in assisting the tax authorities to change the personal and societal perceptions about income tax filing and motivate them to willingly comply with their filing obligations. The study has significant implications for policy making as it identifies a need for government and tax authorities to establish policies and offer incentives and motivational postures that prioritize voluntary compliance rather than introducing sanctions to enforce income tax filing compliance.
Keywords: Tax Education; Taxpayer Perception; Income Tax Filing Compliance; Small Taxpayers